MENELAAH HUKUM PERNIKAHAN MONOGAMI DAN POLIGAMI PERSPEKTIF HADIS - Nadia Nadia; Sapruddin Idris (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2021)
The debate about polygamy and monogamy in Islam has been going on for a long time. This happens because of many interpretations of what has been determined by Al-Qur’an and Al-hadith. Therefore, it is important to review the verse or hadith about polygamy and monogamy. Many problems have arisen related to polygamy at this time. Thus, the history of monogamy and polygamy in Islam is being discussed again by some parties. The author, in this context, examines the aspects of hadith which are the source of law in the Islamic world, apart from of Al-Qur’an which is the main source. Basically, Islam adheres to a monogamous marriage system (tawahhud al-Zauj) but does not forbid polygamy, still allows polygamy with strict limits and conditions.